Feasibility of a Priori Numerical Assessment of Plaque Scaffolding after Carotid Artery Stenting in Clinical Routine: Proof of Concept. Issue 12 (December 2014) - lannaccone, Francesco; De Bock, Sander; De Beule, Matthieu; Vermassen, Frank; Van Herzeele, Isabelle; Verdonck, Pascal; Segers, Patrick; Verhegghe, Benedict
Purpose: Carotid artery stenting (CAS) is an alternative procedure for the treatment of severely stenosed carotid artery lesions in high-risk patients. Appropriate patient selection and stent design are paramount to achieve a low stroke and death rate in these complex high-risk procedures. This study introduces and evaluates a novel virtual, patient-specific, pre-operative environment to quantify scaffolding parameters based on routine imaging techniques. Methods: Two patients who underwent CAS with two different sizes of the Acculink stent (Abbott Vascular, Santa Clara, CA, USA) were studied. Pre-operative data were used to build the numerical models for the virtual procedure. Numerical results were validated with post-operative angiography. Using novel virtual geometrical tools, incomplete stent apposition, free cell area and largest fitting sphere in the stent cell were evaluated in situ as quantitative measures of successful stent placement and to assess potential risk factors for CAS complications. Results: A quantitative validation of the numerical outcome with post-operative images noted differences in lumen diameter of 5.31 ± 8.05% and 4.12 ± 9.84%, demonstrating the reliability of the proposed methodology. The quantitative measurements of the scaffolding parameters on the virtually deployed stent geometry highlight the variability of the device behavior in relation to the target lesion. The free cell area depends on the target diameter and oversizing, while the largest fitting spheres and apposition values are influenced by the local concavity and convexity of the vessel. Conclusions: The proposed virtual environment may be an additional tool for endovascular specialists especially in complex anatomical cases where stent design and positioning may have a higher impact on procedural success and outcome.